The role of structures mangrove in invading sand-mud due to typhoon impact on coastline in Bang La (Do Son) and Dai Hop (Kien Thuy), Hai Phong - Thai, Vu Doan (Academia Journal of Biology, 2012)
Based on study about the role of mangrove forest in Bang La (Do Son) and Dai Hop (Kien Thuy) under acting in the typhoon number two on July 31, 2005, in preventing the muddy sand ridges have investigated and studied. The mangrove forest in Bang La is almost Kandelia obovata Shuen, Lui and Yong (at the seaward edge), and mixing of Sonneratia caseolaris (L) Engl in near shore; with 5-6 year age, average size of 172 cm and 195 cm in height; 76-86 mm in diameter, average density of tree is 17500/ha. In the mixed mangrove forest of Kandelia obovata with 380 cm in height and 121 mm of diameter. Covering of 93-95% area and average density of tree is 400/ha. In Dai Hop (Kien Thuy) there are three kinds of mangrove forest from of shore to on shore in succession of those. The First, Soneratia caseolaris (L) Engl, 5-6 year old, 459 cm in height, 149.5 mm of diameter that covering of 93% area and density of 1351 tree/ha. The second consisting of Kandelia obovata Shuen, Lui and Yong with 165.4 cm of medium height, 90.6mm of diameter that covering of 92% area, density of 16100 tree/ha and the third, near shore mixed consist of mangrove with 410 cm in height, 110.85 mm in diameter, density of 613 tree/ha. The wave height measured at the seaward edge of mangrove of the forest is variation of 1-1.5 m, with wave energy of 212.306 N/m2 that pushed a big of sand-sediment penetrating to the sea shore. However, in presence of the mangrove forest, sediment-sand just has reach to distance of 36-42 m and 55-58 m from edge of the forest in Bang La and Dai Hop, respectively. One to two months later after the typhoon ended, the material from sand bars scattered everywhere in the forest by affected of the wave and tidal current and seemingly no impacts seen along shoreline.